Hydroxyflavone-containing polymers: theoretical prediction of spectral and nonlinear optical properties - Mishurov, D.; Voronkin, A.; Roshal, A. (Functional Materials, 2019)
In order to evaluate spectral and nonlinear optical (NLO) properties of polymers and polymer composites containing natural hydroxyflavones as chain fragments or dopants, a theoretical analysis of absorption spectra of flavones, as well as calculations of values of their first hyperpolarizabilities and bond length alternation coefficients (BLA), were carried out. It has been shown that embedding hydroxyflavone fragments into polymer chains, glycidylation flavone hydroxyl groups, as well as twisting flavone molecules, result in improvement of optical properties of the flavone-containing polymers, namely in widening their transparency range into short-wavelength spectral region. The presence of basic amino-containing hardeners in polymers and polymer composites leads to a partial ionization of the flavone hydroxyl groups and, consequently, narrowing transparency range. The analysis of theoretical values - first hyperpolarizability values and BLA coefficients showed that natural polyhydroxyflavones are perspective chromophores for development of materials having a high NLO activity.